Research Progress of Neutrophil Extracellular Traps in Tumor Metastasis - Xinwei ZHANG; Yong WANG; Yong LI (Chinese Journal of Lung Cancer, 2019)
Recently, studies showed that neutrophils extracellular traps (NETs) are the fiber network structures formed by the materials released by neutrophils under various appropriate stimulation. NETs have been indicated to trap and kill microorganisms, playing a critical role in immune responses. It was pointed out that NETs can not only be involved in inflammation and thrombosis, but also is intimately related to tumor metastasis. Therefore, the study of NETs in tumor metastasis is of great significance for tumor therapy and the progress of NETs in tumor metastasis and the relevant mechanisms is summarized.